2017
DOI: 10.30699/jidai.29.2.51
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Nanocomposites to Dentin Substrate Treated with Er:YAG Laser Followed by Two Different Bonding Systems

Abstract: Background and Aim: Preparation of tooth structure by laser systems produces a surface with different characteristics. Therefore, selecting an appropriate bonding system is necessary to achieve the maximum bond strength. The aim of this study was to compare the bond strength of Adper Single Bond 2 adhesive and Single Bond Universal to dentin prepared by bur or laser. Materials and Methods: In this experimental study, 48 third molars were collected. The enamel was abraded by wet grinding to achieve flat surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Still, the bond strength was significantly lower than that in the bur-prepared groups. 15 In a recent study, Shadman et al found a similar deterioration in the SBS of SU, used in both self-etch and etch-and rinse-modes, to dentin in Er,Cr:YSGG lased dentin groups using 4 W and 5 W output powers than bur-prepared groups, even after 500 thermocycles. 16 Although the results of these two recent studies are in accordance with the SBS of our results, none of these investigations examined the effect of using LMM after LCM.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Still, the bond strength was significantly lower than that in the bur-prepared groups. 15 In a recent study, Shadman et al found a similar deterioration in the SBS of SU, used in both self-etch and etch-and rinse-modes, to dentin in Er,Cr:YSGG lased dentin groups using 4 W and 5 W output powers than bur-prepared groups, even after 500 thermocycles. 16 Although the results of these two recent studies are in accordance with the SBS of our results, none of these investigations examined the effect of using LMM after LCM.…”
Section: Discussionmentioning
confidence: 86%
“…The contradiction of these results can be attributed to the difference in laser type and parameters used. 15,16 However, the influence of LMM dentin surface modification after laser cutting on the bond strength and bond durability was not previously addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations